The Impact of Auditor Switching, Audit Fee and Audit Opinion on Audit Delay with KAP Reputation as a Moderating Variable (Empirical Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange 2022-2024) - Gah, Tiffany NP; Poeh, Melda M. (Journal La Sociale, 2026)
Developments in various business sectors today are marked by the increasing number of companies going public. This forces these companies to compete to provide relevant and timely financial information for use by financial report users (stakeholders). Timely delivery of financial reports means the resulting information can be useful for stakeholders because it provides information for decision-making and can be used for future conditions. This study aims to examine the impact of Auditor Switching. Audit Fee, Audit Opinion, on Audit Delay with Public Accounting Firm Reputation as a Moderating Variable. The research method used is a quantitative method using the SPSS test tool as a data analysis technique. The results of the study indicate that Auditor Switching, Audit Fee, Audit Opinion has an impact on audit delay.